Consumo de antimicrobianos con consideraciones especiales de uso en pacientes hospitalizados del Hospital Regional de Loreto 2019 - Rios Rios, Raul Martin (2022)
Antimicrobials with special considerations for use represent the last line of treatment, therefore, greater control in their consumption is warranted; in order to avoid resistance by microorganisms. Objective: to determine the characteristics of the consumption of antimicrobials with special considerations for use in hospitalized patients of the Regional Hospital of Loreto, period 2019. Methodology: The study was descriptive and the consumption of antimicrobials prescribed to patients of the surgery, gynecology, infectology, medicine and obstetrics, through the defined daily dose. Results: 67.7% of patients treated with antimicrobials with special considerations for use were female, 44.36% of patients were between 30 and 59 years of age, with the month of March being the month with the highest prescription (10.05%) and the most consumed antimicrobial per unit was ceftriaxone sodium 1g (41.5%) with an annual defined daily dose of 1.2704, followed by metronidazole 500mg/100mL with 0.2990 and ciprofloxacin 200mg with 0. 2,874 per 100 bed-days, respectively; the antimicrobial with the highest cost per consumption was meropenem (39.79%). Conclusions: the antimicrobials with special considerations for use prescribed in all hospitalization services totaled 22,983 units, the antimicrobials with the highest consumption per unit were ceftriaxone, meropenem and vancomycin, as well as the drug with the highest defined daily dose/ 100 bed-days were ceftriaxone, metronidazole and ciprofloxacin, likewise the antimicrobial with the highest monetary value were meropenem, ceftriaxone and vancomycin.